The Relationship between the New and the Old Testament - Ghiuta, Stefan-Adrian (Eximia, 2022)
The Christian religion conceives of God as a personal being who does not remain distant or indifferent to creation, but is in connection with it, especially with man, the pinnacle of creation. Thus God communicates to people so that they can know at least in part something about Him and also so that they can know His will and plans in relation to creation and especially in relation to Him. God revealed himself to people in two ways: through natural Revelation, emphasizing man's character as a rational being, and through supernatural Revelation, without which man could not understand the natural one. Likewise, the Revelation was realized throughout the ages, throughout the history of mankind, starting with the discovery made to the first people and culminating with the one given by Jesus Christ. The supernatural divine revelation was transmitted to us in two ways: Holy Scripture and Holy Tradition. We will learn the importance of preserving the Holy Scriptures unaltered, as the source from which Christianity drew the sap of its teachings and found its support throughout its history. We will try to present the fact that the Holy Scripture is a precious help in understanding the divine message and in putting into practice a Christian life that will lead the believer on the path of the Kingdom. It is important that by leaning towards the Holy Scriptures, the Christian should stay on the path of salvation, in the Church, having as an example the Holy Apostles, keepers of Tradition and Scripture, but also their transmitters. Only by intertwining these two ways through which we have the unaltered word of God will we be able to say that we are in the Church of Christ. Only by keeping unaltered the truths contained in Holy Scripture and especially by fulfilling them, we are in Christ and in His mysterious Body - the Church - because Scripture, along with Tradition, was and will be the norm of Christian life until the end of time. That is why we considered it necessary to present the value and importance of the Holy Scripture in its entirety on the foundation of Christian teaching, as well as on its living in the Church. Christ revealed by the Scriptures communicates to people. The Scriptures put and keep Christians in relation to Christ, especially due to the fact that Revelation projects its final goal in eternal communion with the person of Christ, a goal towards which we also advance through our efforts in relations with other people, and this goal is shown in a concentrated manner by the Holy Scripture, the Holy Tradition explaining at every step this road virtually included in the Revelation, as a road leading to the goal of our perfection in Christ. We hope that by researching, as much as possible, the specialized works and studies in theological publications, we will present the importance of the Holy Scriptures as a means of transmitting the saving truth, but also the importance of intertwining the teachings contained in them for a better knowledge and application of divine truths in the Christian life, in The church.